Pembimbingan Dalam Pembuatan Prototipe Project D-Therwaste untuk Lomba IDEX 2023 yang diselenggarakan oleh Anglo-Chinese School (Independent) Singapore - Demas Sabatino; Iwan Setyawan; Sirilus Widi Surya Pranata (Cv. Utility Project Solution, 2023)
Innovation is the key to a developed country, and it needs to start as early as possible. SMP Kristen Gloria 2 Surabaya implements this through its participation in IDEX 2023, an innovation competition for the 13-18 year old category. To get the best results, SMP Kristen Gloria 2 Surabaya collaborated with the Fakultas Teknik Elektronika dan Komputer Satya Wacana (FTEK UKSW) Salatiga in terms of consulting and mentoring the teams participating in the competition. The FTEK UKSW service method for partners in the form of consultation and guidance is carried out from selecting ideas, deepening material, making and testing prototypes, until the competition ends. The idea chosen is to convert electricity using a heat energy source that is wasted from a gas stove using a thermoelectric generator (TEG). Where the gas stove is a household appliance that is commonly found in households and food/beverage sellers. The prototype made can charge the power bank by utilizing the dc-to-dc converter module with input from TEG. The innovation made by this team won recognition in the form of a silver medal and the James Dyson Foundation (Innovation Category) at the IDEX 2023 event organized by Anglo-Chinese School (Independent) Singapore.